Jóvenes migrantes e hijos de inmigrantes latinoamericanos en Buenos Aires: una generación en movimiento - Gavazzo, Natalia (Confluenze. Rivista di Studi Iberoamericani, 2018)
This article is based on a research among immigrants’ descendants in Buenos Aires that examines their practices and imaginaries related to their ancestors and places of origin, and on the ways in which they affect their current political practices. It examines a recent movement, created by young migrants and descendants of Latin America immigrants who – beyond their internal diversity – have a generational discourse that not only differentiate them from previous others but also turn them into a central actor in the context of current changes of Argentine political and migratory culture.